Development of a Real Time Three Phase Power Parameter Monitoring System Using Programmable Logic Controller (PLC) and Internet of Think (IoT) - Nur Azhary Iriawan Eka Putra; Andi Fitriati; Akhyar Muchtar; Nurhikmah Fajar (Jurusan Pendidikan Teknik Elektro, 2025)
This study presents the development of a real-time three-phase electrical power monitoring system based on a digital power meter, Programmable Logic Controller (PLC), Human–Machine Interface (HMI), and Internet of Things (IoT) technology. The proposed system was designed to acquire key electrical parameters, including voltage, current, and frequency, and to display the measured data consistently for both local monitoring via an HMI and remote monitoring through IoT-enabled devices. Data acquisition from the power meter was performed using Modbus RTU communication, with the PLC acting as the central data processing and control unit, and the HMI and IoT platforms provided visualisation and remote access. The system implementation and testing were performed under different load conditions to evaluate the functionality, data consistency, and communication reliability. The experimental results show that the measurement values displayed on the HMI and IoT platforms are identical, indicating stable data communication and correct register mapping. Minor differences between the power meter readings and the monitoring system were observed, with a maximum error of 0.6195 %, which was attributed to the display resolution and rounding limitations of the power meter rather than data processing errors. The results demonstrate that the developed system is reliable and accurate for real-time three-phase power-monitoring applications. The integration of industrial devices with IoT technology enhances data accessibility, improves the visibility of electrical system conditions, and supports modern monitoring requirements, making the proposed system suitable for industrial and technical facility applications.